1996
DOI: 10.1093/ptj/76.8.827
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders Among Physical Therapists

Abstract: Specific strategies should be developed to reduce WMD in the practice of physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
247
12
47

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(350 citation statements)
references
References 11 publications
44
247
12
47
Order By: Relevance
“…5% in Cromie et al 9) , 69% in Molumphy et al 16) , 67% in Campo et al 14) , 73% in Glover et al 12) , 77.1% in Nordin et al 21) , and 80.0% in Bork et al 10) . Studies of WRMD prevalence in physical therapists in different countries indicate a prevalence of 47.6% in Kuwait 19) , 53.5% in Sweden 20) , 57.5-61% in the United States 10,14) , 67.5% in the United Kingdom 12) , 71.6% in Malaysia 21) , 85.0% in Turkey 1) , 54.8-91% in Australia 9,11) , and 91.3% in Nigeria 15) . The causes of WRMD included lack of personnel, bad working environments, and lack of equipment to reduce the burden on the body.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…5% in Cromie et al 9) , 69% in Molumphy et al 16) , 67% in Campo et al 14) , 73% in Glover et al 12) , 77.1% in Nordin et al 21) , and 80.0% in Bork et al 10) . Studies of WRMD prevalence in physical therapists in different countries indicate a prevalence of 47.6% in Kuwait 19) , 53.5% in Sweden 20) , 57.5-61% in the United States 10,14) , 67.5% in the United Kingdom 12) , 71.6% in Malaysia 21) , 85.0% in Turkey 1) , 54.8-91% in Australia 9,11) , and 91.3% in Nigeria 15) . The causes of WRMD included lack of personnel, bad working environments, and lack of equipment to reduce the burden on the body.…”
Section: Discussionmentioning
confidence: 93%
“…The low back is the body part with the highest WRMD prevalence, having been reported as 26% by Salik and Ozcan 1) , 28.8% by Molumphy et al 16) , 32.0% by Alrowayeh et al 19) , 35% by West and Gardner 11) , 45.0% by Bork et al 10) , 44% by Glover et al 12) , 51.7% by Nordin et al 21) , 56.5% by Grooten et al 20) , 62.5% by Cromie et al 9) , and 69.8% by Adegoke et al 15) Shehab et al 22) observed that lifetime WRMD prevalence rate was 70% among physical therapists with low back pain patients, because physical therapists handled their patients using inappropriate body mechanics and wrong techniques. Nordin et al 21) observed that physical therapists using manual treatments experienced more stress in the spine than in the hands because they applied manual treatments in the standing position over a long time.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations